Implementasi Metode Whole Language untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa Kelas X MAN Insan Cendekia Siak Riau - Huda, Rezki Riadhul (MAN Insan Cendekia Siak, 2025)
This study investigates whether the application of the Whole Language method can improve Arabic learning outcomes among Grade X students at MAN Insan Cendekia Siak, Riau. Employing a quantitative approach, data were collected through observation to examine the implementation of the method and tests to measure student learning outcomes. Data were analyzed using a t-test within a post-test-only nonequivalent groups design comprising control and experimental classes. The study population included all 144 Grade X students, from which a sample of 33 students was determined using the Slovin formula. The findings indicate that the Whole Language method significantly improve Arabic learning outcomes, as evidenced by a t-statistic of 4.70 exceeding the t-table values at the 1% (2.80) and 5% (2.10) significance levels. The implementation reached 96.8% and categorized as excellent, demonstrating that the method was applied with high quality. These results support the effectiveness of the Whole Language approach in improving students’ Arabic achievement at the upper-secondary level.